(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
Now, more than any other time in our history, technology has connected cultures, radically increasing the opportunities for contact between peoples across the globe. Religions are converging as never before, corporate conglomerations are multiplying, and differing economic and political systems are increasingly pitted against each other. Earth’s resources are siphoned, patented, and commodified. This modern menagerie of cultures and worldviews creates for many an incomprehensible atmosphere of multiplicity and chaos that demands increasingly adapted ethics and values. In the shadow of this reality, the Earth Charter’s preamble opens with the proclamation: ‘We stand at a critical moment in history.’ What is this critical moment? It is a global-industrial society aborting its vital umbilical connections to the Earth. It is a greed-driven consumer culture that abandons humanity in search of wealth, and in doing so starves others in so-called ‘third-world’ conditions. Where are we now? How did we get here? And where do we go?